A Forensic Evaluation of Ligature Implements in Suicidal Hanging Death - Haque, Marina; Rony, Md Shyful Islam (Journal of Brahmanbaria Medical College, 2026)
Background: Suicide is one of the commonest causes of death worldwide and has a great public health effect. Hanging is the most preferred method of suicide. The choice of method depends on the accessibility and availability of the means on the spot at the time of act. However, the type of materials used and position of the knot plays an important role in the mechanism of the death and autopsy findings in hanging. The present study was conducted with objective to study the choice of ligature material preferred for hanging and the type of hanging in relation to point of suspension and others associated factors. Materials and methods: The present study is a retrospective analysis of 159 post mortem cases of suicidal hanging at Dhaka Medical College over a period of January 2018-December 2019. To understand suicidal hanging by studying different parameters involved in it like ligature materials, sex and age and position of knot and ligature marks. The results are analyzed on the basis of history, postmortem findings and results laboratory investigations. Results: The age group 21-30 was found to be the most prevalent (37.10 %) for suicidal hanging. The majority of the victims were male contributing to (59.75%) of the death. Most commonly used ligature material was Rope (61.00%) followed by Orna (15.72%). The nature of ligature material was soft in (66.04%) cases. Most victims had complete suspension (72.33%). The ligature mark was oblique shaped in (97.48%) cases. Conclusions: The commonly used ligature was a rope. Rope is easily available in almost every hanging. The different parameters of suicidal hanging are necessary to understand the suicidal nature of hanging. JBRMC, Volume 08 Issue 01 January 2026 ; 37-40